High Power Output Microbial Fuel Cell using Nitrogen and Iron Co‐Doped Carbon Nanospheres as Oxygen‐Reduction Catalyst. Issue 9 (20th June 2017) - Shi, Xinxin; Zhang, Jiaona; Huang, Tinglin
Abstract: Microbial fuel cells (MFCs), widely recognized as a promising technology, naturally combine the functions of green energy generation and wastewater treatment. Developing effective catalysts for the cathodic oxygen reduction reaction (ORR) to improve the power outputs of MFCs has aroused extensive research interests. To achieve a high‐performance MFC, low‐cost nitrogen and trace iron co‐doped porous carbon nanospheres (NFe/CNS) were synthesized in this work by using a facile method. The MFC using NFe/CNS as an ORR catalyst showed a maximum power density of 866.5±7 mW m −2, which is 24 % higher than that of a MFC using Pt/C as a catalyst. Moreover, compared with Pt/C, NFe/CNS demonstrated a stronger tolerance against acetate (a typical anodic fuel in MFCs) crossover and durability in the MFC neutral electrolyte. Benefiting from the outstanding catalytic properties of NFe/CNS, the normalized energy recovery of the MFC with NFe/CNS was two times higher than that of the MFC with Pt/C. These results demonstrated that NFe/CNS could be expected to be a practical and breakthrough catalyst for MFCs. Abstract : Cheap and high performance : Low‐cost nitrogen and trace iron co‐doped porous carbon nanospheres (NFe/CNS) are synthesized using carbon black as the support. The NFe/CNS display superior catalytic activity, tolerance against acetate crossover, and durability than Pt/C. Microbial fuel cells (MFCs) using NFe/CNS as oxygen‐reduction catalysts exhibit outstanding maximum power density and normalized energy recovery (NER), 24 % and two times higher, respectively, than that of Pt/C‐based MFCs.